The Development of Teacher and Educational Personnel Promotional Assessment Framework in Thailand - TAMRONGLAK, AMPORN (Jurnal Studi Pemerintahan, 2013)
The main purpose of this paper is to present a per-formance evaluation framework for teacher and edu-cational personnel inThailand. Based on the re-search funded by Office of the Teacher Civil Service and Educational Personnel Commission, it isaimed primarily to study the model of academic standing assessment of teacher civil service and educational personnel and todevelop criteria and methods for the four tracks of personnel in Thailand, including teaching, educational institutionadministration, educational administration, and educational super-vision. Various methods in gathering data for the study wereemployed, including 1) documentary re-search of four different countries, such as United States of America, England, Singaporeand HongKong; 2) site visits to the government agencies re-sponsible for educational assessment and develop-ment and schoolsin Hong Kong and Singapore; 3) in-depth interviews with Executives in Ministry of Education and a number of stakeholders whohad requested for the promotional assessment from all four career tracks; 4) focus group method among experts in the field; and5) public hearing opened to all stakeholders in teaching careers was also orga-nized to gather comments and suggestions andfine-tune the proposed framework prior to submission to the Office of the Teacher Civil Service and Educa-tional PersonnelCommission for further application in the future.KEYWORDS: Performance evaluation, PromotionalAssessment Framework, Academic ranking assess-ment of teacher in Thailand